Susceptibility of Gardnerella vaginalis Biofilms to Natural Antimicrobials Subtilosin, ε-Poly-L-Lysine, and Lauramide Arginine Ethyl Ester - Yevgeniy Turovskiy; Thomson Cheryian; Ammar Algburi; Ruth E. Wirawan; Paul Takhistov; Patrick J. Sinko; Michael L. Chikindas (Hindawi Limited, 2012)
Bacterial vaginosis is a common vaginal infection associated with numerous gynecological and obstetric complications. This condition is characterized by the presence of thick adherent vaginal biofilms, composed mainly of Gardnerella vaginalis. This organism is thought to be the primary aetiological cause of the infection paving the way for various opportunists to colonize the niche. Previously, we reported that the natural antimicrobials subtilosin, ε-poly-L-lysine, and lauramide arginine ethyl ester selectively inhibit the growth of this pathogen. In this study, we used plate counts to evaluate the efficacy of these antimicrobials against established biofilms of G. vaginalis. Additionally, we validated and compared two rapid methods (ATP viability and resazurin assays) for the assessment of cell viability in the antimicrobial-treated G. vaginalis biofilms. Out of the tested antimicrobials, lauramide arginine ethyl ester had the strongest bactericidal effect, followed by subtilosin, with clindamycin and polylysine showing the weakest effect. In comparison to plate counts, ATP viability and resazurin assays considerably underestimated the bactericidal effect of some antimicrobials. Our results indicate that these assays should be validated for every new application.